Developments in a dedicated salivary gland centre: a 10‐year retrospective review. (11th August 2018) - Samani, M.; Modgill, O.; Atiea, T.; Cheales, E.; Shokouhi, B.; Beheshti, S.; McGurk, M.
Abstract: Diseases of the salivary glands are uncommon and patients present to a number of specialties. The result is that experience is thinly spread across clinical specialities. A dedicated salivary gland clinic was set up at Guy's Hospital London fifteen years ago. The profile of patients referred to the centre over the last ten years was analysed and changes in management mapped over time with respect to methods of investigation and treatment. Gland removal, which was previously the treatment of choice for most benign salivary gland diseases has been replaced by gland sparing procedures which have rendered gland excision to a minor role in management. Salivary gland surgery‐related morbidity has been markedly reduced.